Rural-urban disparities in healthcare factors and long-term health outcomes in individuals with pediatric-onset spinal cord injury - Kyle C. Deane; Kyle C. Deane; Nikhil Kurapati; Emma Gill; Lawrence C. Vogel; Lawrence C. Vogel; Kathy Zebracki; Kathy Zebracki; Kathy Zebracki (Frontiers Media S.A., 2023)
ObjectiveAdults with pediatric-onset spinal cord injury (SCI) require long-term care and demonstrate elevated risk of secondary health conditions and psychosocial challenges. Medical providers are typically found in more populous and wealthy areas, resulting in a relative lack of providers in rural areas, a discrepancy even more pronounced among specialty providers. As a result, those who reside in rural regions potentially have unmet medical needs, representing a significant public health concern. The purpose of this study was to assess differences between rural and urban-residing participants with pediatric-onset SCI in factors affecting healthcare usage (e.g., employment, income, access to private insurance, community integration) and long-term healthcare outcomes (i.e., secondary health conditions and psychosocial functioning).MethodsData were gathered from an ongoing study examining long-term outcomes of adults with pediatric-onset SCI. Participants (N = 490) completed measures of sociodemographics, injury characteristics, and medical outcomes. Participant zip codes were classified as rural or urban using the ProximityOne database based on the ZIP Code Tabulation Areas from the 2020 census.ResultsIndividuals residing in rural regions report lower levels of education, income, employment rates, private health insurance, and community integration (mobility, occupation, and social engagement), as well increased incidence of pressure injuries, urinary tract infections, hospitalizations, bowel incontinence, sleep difficulties, and perceived physical health. No differences in incidence of psychosocial functioning were identified.ConclusionMitigating identified disparities and obstacles to treatment of SCI due to residing in rural environments would result in important improvements in treatment outcomes and future prevention efforts of secondary health complications, improving the overall health of adults with pediatric-onset SCI.